2018
DOI: 10.3390/ma11040544
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Behaviors of Titanium Matrix Composites Containing In Situ Whiskers Synthesized via Plasma Activated Sintering

Abstract: In this paper, titanium matrix composites with in situ TiB whiskers were synthesized by the plasma activated sintering technique; crystalline boron and amorphous boron were used as reactants for in situ reactions, respectively. The influence of the sintering process and the crystallography type of boron on the microstructure and mechanical properties of composites were studied and compared. The densities were evaluated using Archimedes’ principle. The microstructure and mechanical properties were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These groups of alloys have the potential for use in temperatures up to 700°C, but still maintain better strength and ductility. TiB W /Ti-1100 (Chandravanshi et al , 2011; Ma et al , 2017a), TiB W /Ti-64 (Roy and Suwas, 2014; Sun et al , 2018b; Wang et al , 2012), TiB W /VT18U (Gaisin et al , 2017), TiB W /IMI834 (Prasad et al , 2011b) and TiB W /Ti-60 (Wang et al , 2015b) have been investigated for mechanical properties at room and high temperature conditions. The research reported significant grain refinements coupled with superior tensile strength and elongations compared to their base alloys at both temperatures.…”
Section: Mechanical Properties Of Near-α Titanium Alloysmentioning
confidence: 99%
“…These groups of alloys have the potential for use in temperatures up to 700°C, but still maintain better strength and ductility. TiB W /Ti-1100 (Chandravanshi et al , 2011; Ma et al , 2017a), TiB W /Ti-64 (Roy and Suwas, 2014; Sun et al , 2018b; Wang et al , 2012), TiB W /VT18U (Gaisin et al , 2017), TiB W /IMI834 (Prasad et al , 2011b) and TiB W /Ti-60 (Wang et al , 2015b) have been investigated for mechanical properties at room and high temperature conditions. The research reported significant grain refinements coupled with superior tensile strength and elongations compared to their base alloys at both temperatures.…”
Section: Mechanical Properties Of Near-α Titanium Alloysmentioning
confidence: 99%
“…Based on the volume fraction 8.5% TiB whisker-reinforced titanium matrix composites in the literature [15], spherical TC4 powder with a particle size of 120–220 μm and TiB 2 powders with a particle size of 1–5 μm were mixed at a certain ratio, then TiB w /TC4 composites were prepared by high temperature hot pressing sintering. The TC4 powder softened and densified between the particles due to the high temperature and the original spherical TC4 powder became a polyhedron.…”
Section: Finite Element Analysis Of Tibw/tc4 Compositesmentioning
confidence: 99%
“…1 However, the high compressive properties of PM titanium composites containing in-situ whiskers have been reported. 6 AM technology is characterized by its layer-by-layer manufacturing method, also widely known as 3D printing, providing metallic components with improved accuracy and surface finish with less set-ups. 7,8 AM fabrication methods are classified into a powder bed system, powder feed system, as well as a wire feed system.…”
Section: Introductionmentioning
confidence: 99%